If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + 2) = 10 Reorder the terms: 5(2 + c) = 10 (2 * 5 + c * 5) = 10 (10 + 5c) = 10 Add '-10' to each side of the equation. 10 + -10 + 5c = 10 + -10 Combine like terms: 10 + -10 = 0 0 + 5c = 10 + -10 5c = 10 + -10 Combine like terms: 10 + -10 = 0 5c = 0 Solving 5c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '5'. c = 0 Simplifying c = 0
| 99x+x-88=31+11-40 | | 4v^2-12v+9=0 | | 3e=24 | | 851*8= | | 5x-3x-5x=-2+18 | | 24x+15=60x-20 | | 30+2x=15 | | 24x=60x | | 0.5m=3 | | 2x+2y=950 | | 6x+9-3x=6x+4 | | y-14=26 | | x^2+6x+9-5x-15+4=0 | | 79x=9796 | | 6x-1x=28-13-13 | | 4x+6=12-5x | | 2k^2+6k+9=0 | | 2x+(x-20)+x=180 | | 2k^2+6k=-9 | | 6b+2t=232 | | 4(2+1)=2(3-x) | | 26=-16x^2+4x+16 | | 5p+7=3(4-q) | | 4n-5=3 | | x*x-18x+81=4+81 | | -14=-(-2+2) | | -x*x+x+.25=1.25 | | 2m+6=2(2m+3)-2 | | -x*-x+x+.25=1.25 | | 3(c-8)+13=5c+5 | | -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) |